Pitfalls in mitochondrial epigenetics. (3rd September 2017) - Pawar, Tina; Eide, Lars
Abstract: 5-Methylcytosine (5mC) and 5-hydroxymethylcytosine (5hmC) are fingerprints of epigenetic modifications. These bases have been found in the mitochondrial DNA (mtDNA) and together with the discovery of mitochondrial localization of DNA methyltransferases, this implies that mtDNA is under epigenetic regulation. However, the indirect methods hitherto used to assess mitochondrial 5mC and 5hmC require attention as they readily generate artificial signals that may lead to erroneous conclusions. Here, we demonstrate how three independent, frequently used methods to identify epigenetic modification of DNA readily generate false mtDNA epigenetic signals. The three methods were selective 5mC/5hmC-mediated inhibition of restriction enzymes, bisulfite conversion and 5hmC glucosylation-dependent immunocapture. Adequate controls for all methods are suggested.